Primary Care Physicians and Disparities in Colorectal Cancer Screening in the Elderly - Singal, Ashwani K (Blackwell Science Inc, 2013)
OBJECTIVE: To examine whether having a primary care physician (PCP) is associated with reduced ethnic disparities for colorectal cancer (CRC) screening and whether clustering of minorities within PCPs contributes to the disparities. DATA SOURCES/STUDY SETTING: Retrospective cohort study of Medicare beneficiaries age 66–75 in 2009 in Texas. STUDY DESIGN: The percentage of beneficiaries up to date in CRC screening in 2009 was stratified by race/ethnicity. Multilevel models were used to study the effect of having a PCP and PCP characteristics on the racial and ethnic disparities on CRC screening. DATA COLLECTION/EXTRACTION METHODS: Medicare data from 2000 to 2009 were used to assess prior CRC screening. PRINCIPAL FINDINGS: Odds of undergoing CRC screening were more than twice as high in patients with a PCP (OR = 2.05, 95 percent CI 2.03–2.07). After accounting for clustering and PCP characteristics, the black–white disparity in CRC screening rates almost disappears and the Hispanic–white disparity decreases substantially. CONCLUSIONS: Ethnic disparities in CRC screening in the elderly are mostly explained by decreased access to PCPs and by clustering of minorities within PCPs less likely to screen any of their patients.